El significado de los adelantos recientes en el campo de la comunicación masiva - Robert A. White (Estudios sobre las Culturas Contemporáneas)
R. White talks about the three main trends in the mass media and how these are being developed as consensual topics in three main research scopes: a) the traditional empirical-positivist-quantitative, b) the traditional sociopolitcal marxist analysis, and c) the cultural and anthropological communication studies.